THE MODERN VIEW ON PATENT DUCTUS ARTERIOSUS IN PRETERM INFANTS - Звягина, Жанна Анатольевна; Цой, Елена Глебовна; Игишева, Людмила Николаевна; Тронина, Дарья Андреевна (Mother and Baby in Kuzbass, 2018)
Objective – to study the influence of the functioning arterial duct on the development of premature babies with extremely low and very low body weight.Materials and methods of the research. The evaluation of the information databases of the Cochrane system, PubMed, Liters, Key words (search words): «patent ductus arteriosus in premature infants», and «outcomes of premature infants». The search depth was 22 years (1996-2018).Results. More than 1,500 publications found. Complied with the selection criteria of 42 publications.The present literature review analyzes the current information on the influence of the patent ductus arteriosus (PDA) in preterm infants with extremely low (ELBW) and very low body weight (VLBW), approaches to the diagnosis of hemodynamic significance of the patent ductus arteriosus, tactics of choice of therapy of the patent ductus arteriosus in premature infants with extremely low and very low body weight. Hemodynamically significant PDA (hsPDA) in deeply premature children contributes to the development of severe complications and can lead to death. Priority in the choice of treatment hs PDA in neonatal period is given to his medical closure using cyclooxygenase inhibitors. However, despite the high efficiency (up to 70-80 %), conservative therapy of hs PDA may also be accompanied by the development of a number of complications. According to the literature, 73 % of newborns with VLBW and ELBW observed spontaneous closure of the ductus arteriosus.Conclusion. A functioning PDA may contribute to a high incidence of morbidity in preterm with ELBW and VLBW. Indications to medical and surgical its closure, both methods have theiradvantages and disadvantages, but a common approach in the choice of a particular method of treatment to date, no. Given the spontaneous closure of PDA in 73 % of premature infants with VLBW and ELBW, it is advisable to use a wait-and-see tactic with regard to the treatment of hs PDA.
Keywords: preterm infants; patent ductus arteriosus; very low body weight; extremely low body weight